Penyuluhan Literasi Membaca Menggunakan Media Papan Antonim Pada Siswa Kelas 2 di SDS NU Kencong - Isnaini Nur Azizah; Astri Widyaruli Anggraeni (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
This research aims to improve reading literacy using Antonin board media in class 2 of SDS NU Kencong in the 2022/2023 academic year. The method used is to carry out community service through 5 stages, namely observation, formulating problems, creating materials, carrying out counseling and evaluation. As a result of the counseling using antonym board media, students became active and enthusiastic in participating in learning, but there were some students who had difficulty reading due to their lack of familiarity with reading. This antonym board media makes the learning process fun and interesting. This is an innovation to increase students' interest in reading literacy. In the future, it is hoped that there will be further innovation regarding learning media with the target of teachers being able to help students enjoy reading.